2019
DOI: 10.1038/s41598-019-51417-0
|View full text |Cite
|
Sign up to set email alerts
|

Human beings as islands of stability: Monitoring body states using breath profiles

Abstract: By checking the reproducibility of conventional mid-infrared Fourier spectroscopy of human breath in a small test study (15 individuals), we found that a set of volatile organic compounds (VOC) of the individual breath samples remains reproducible at least for 18 months. This set forms a unique individual’s “island of stability” (IOS) in a multidimensional VOC concentration space. The IOS stability can simultaneously be affected by various life effects as well as the onset of a disease. Reflecting the body sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 56 publications
0
43
0
Order By: Relevance
“…As none of the participants in the C22_14 dataset were smokers this cluster is relatively well isolated from the network ( Supplementary Figure 11 ). Nonetheless, breath profiles including CO and NO have been proposed for monitorization of whole body states ( Maiti et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…As none of the participants in the C22_14 dataset were smokers this cluster is relatively well isolated from the network ( Supplementary Figure 11 ). Nonetheless, breath profiles including CO and NO have been proposed for monitorization of whole body states ( Maiti et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The instrument and its performance for real breath samples are described in refs. [13,14], and we therefore only present its key parameters here. We used a Fourier spectrometer Bruker Vertex 70 operating in a spectral range of 500-4000 cm −1 in conjunction with a 4 meter 2 liter "White cell" (Bruker) that collects breath for the measurement, and a liquid nitrogen cooled MCT detector.…”
Section: The Spectroscopic and Breath Collection Techniquesmentioning
confidence: 99%
“…The participants were chosen based on our previous results [14], in order to properly match the diseased group. We found that a smoking habit as well as high methane emission in breath of all the volunteers [14] do not affect the data in the spectral range shown in Figure 1. Note: Gross Motor Function Classification System distinguishes a patient's degree of self-initiated movement abilities, and varies from level I (easy) to level IV (difficult).…”
Section: A Description Of the Patients And The Reference Groupmentioning
confidence: 99%
See 2 more Smart Citations